Trends in nitrate contamination: implications for communities reliant on groundwater for drinking - D Harshanee Jayasekera; Siddhi Munde; Daniel D Snow; Renata Rimšaitė (Environmental Research Communications)
Nebraska’s vulnerability to nitrate contamination in water systems is highlighted by agrochemical inputs with leaching potential and the state’s reliance on groundwater for drinking. Nitrate is a regulated compound in drinking water due to its association with methemoglobinemia and other chronic health conditions. This study examines water quality in Nebraska’s groundwater over several decades, focusing on temporal and spatial variations in nitrate concentrations across different well types. The findings reveal increasing statewide trends in nitrate levels, with considerable spatial variability. Private-domestic wells, particularly in agricultural areas, are more susceptible to contamination. These trends suggest a growing risk for communities without access to regulated public water systems. The study emphasizes the need for targeted interventions in vulnerable regions, and provides insights into the broader implications of agricultural contaminant leaching on groundwater quality and public health.